Three new features of innovation brought about by information and communication technology. (1st September 2004) - Lan, Ping
This paper aims to examine the changes to innovation brought about by the internet. Based on a systematic survey on the current efforts made by industry and academia in expanding the frontier of innovation, it found that e-innovation – add-on or collective changes to innovation brought about by Information and Communication Technology – is expanding traditional innovation in three aspects: 1) having an obvious tendency to software development and application, 2) encouraging a distributed delivery, and 3) deploying different managing/operating rules and toolkits. These expansions are leading e-innovation to become a new paradigm for carrying out creative activities.